A Preliminary Study on Prevalence of Hepatic Disorders in Dogs in Indore District (M.P.) - Kambhkar, Yogesh; Bagherwal, RK; Mehta, HK; Badsar, Pooja (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was carried out on 1082 dogs presented to department of Veterinary Medicine, Teaching Veterinary Clinical Complex (T.V.C.C.) college of Veterinary Science & A.H. Mhow .The dogs were examined clinically and haemato-biochemically in order to assess the hepatic disorders. The prevalence of hepatic disorders among screened dogs was found to be 3.51%. The highest (36.84%) prevalence was observed between 4 to 8 years of age. Sex wise prevalence showed that females were more (57.89%) susceptible than males (42.11%) among all breeds. The most affected breed was Labrador Retriever (21.06%) followed by Pomeranian, Non-descript, German Shepherd, Crossbreed, Rottweiler, Great Dane, Saint Bernard and Golden retriever.